Analysis of the effects of malaria chemoprophylaxis in children on haematological responses, morbidity and mortality - Geerligs Paul D. Prinsen; Brabin Bernard J.; Eggelte Teunis A. (The World Health Organization, 2003)
This paper reviews the evidence for beneficial effects of malaria chemoprophylaxis on haematological responses, morbidity, mortality, health service utilization and rebound immunity in children. As anaemia may play an important role in childhood mortality, it is important to assess evidence from controlled trials of the potential of chemoprophylaxis to reduce childhood anaemia. An analysis of trials found good evidence that malaria chemoprophylaxis improves mean haemoglobin levels and reduces severe anaemia, clinical malaria attacks, parasite and spleen rates. Significant reductions in outpatient attendance and hospital admissions have been achieved, and substantial evidence from Gambian studies shows reductions in mortality. Chemoprophylaxis in children does not seem to produce any sustained impairment of immunity to malaria, although rebound effects may be greater in children who receive prophylaxis during infancy. Short periods of targeted prophylaxis are likely to be preferable to continuous drug administration. Evidence of the protective efficacy of malaria chemoprophylaxis in children shows that this strategy could be considered within integrated health programmes for specific time periods. Intermittent routine combination therapy early in childhood may be appropriate for those living under holoendemic conditions. Large-scale studies over a number of years are needed to address this issue and the impact of this approach on health service utilization, mortality, and the emergence of drug-resistant parasites.